Branched chain amino acids metabolism in heart failure - Gao, Chenshan; Hou, Lei (Frontiers in Nutrition, 2023)
As a terminal stage of various cardiovascular diseases, heart failure is of great concern due to its high mortality rate and limited treatment options. Researchers are currently focusing their efforts on investigating the metabolism of carbohydrates, fatty acids, and amino acids to enhance the prognosis of cardiovascular diseases. Simultaneously, branched-chain amino acids (BCAAs), including leucine, isoleucine, and valine, play significant roles in blood glucose regulation, protein synthesis, and insulin sensitivity. However, disrupted BCAAs metabolism has been associated with conditions such as hypertension, obesity, and atherosclerosis. This article explores intricate metabolic pathways, unveiling the connection between disrupted BCAAs metabolism and the progression of heart failure. Furthermore, the article discusses therapeutic strategies, assesses the impact of BCAAs on cardiac dysfunction, and examines the potential of modulating BCAAs metabolism as a treatment for heart failure. BCAAs and their metabolites are also considered as biomarkers for evaluating cardiac metabolic risk. In conclusion, this article elucidates the multifaceted roles of BCAAs in heart failure and cardiovascular health, providing guidance for future research and intervention measures.